Supporting allies in counterinsurgency : Britain and the Dhofar Rebellion - Ladwig, W (Routledge, 2008)
From 1964 to 1975 a small group of British officers, advisors, and trainers guided the forces of the Sultanate of Oman to victory in their conflict with the Marxist insurgents of the People's Front for the Liberation of the Occupied Arabian Gulf (PFLOAG). This campaign provides a clear example of how to effectively support an ally's counterinsurgency efforts with a minimal commitment of men and material. In particular, the critical assistance provided by the British consisted of experienced leadership and skilled technical support personnel as well as a viable strategy for victory. However, more important for the ultimate success of the counterinsurgency campaign was the emergence of new progressive leadership with the accession of Sultan Qaboos. The most important lesson from this study is that while security assistance can reinforce positive political efforts, it is not enough on its own to bring about a victory in an unfavourable political environment.